A ceramic conveyor belt for coking and preparation method thereof
By using a multi-layer fiber braided structure and a ceramicized cover layer in the ceramic conveyor belt for coking, the existing heat-resistant and high-temperature conveyor belt is easily scalded and burned through under high temperature environments, and a higher level of Durability and service life.
Patent Information
- Application Number
- CN202411330129.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-24
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-09-24
AI Technical Summary
The heat-resistant and high-temperature resistant conveyor belts used in the existing coking industry are prone to burning, burning through or even burning in high temperature environments, with a short life and need to be replaced frequently.
Using a skeleton layer with a multi-layer fiber braided structure and a double-layer structure covering layer, hydrogenated nitrile rubber, neoprene, polyimide, ceramic initiator and flame retardant are added to the upper cover layer to form ceramic Structure to improve high temperature resistance and flame retardant properties.
Under continuous high temperature environment, the ceramicized rubber layer of the conveyor belt can form a small ceramic sheet structure, which can dissipate heat and wear resistance, significantly improve the durability and service life of the conveyor belt, avoiding burning, burning and Burning defects.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of conveyor belts, and in particular to a ceramic conveyor belt for coking and a preparation method thereof. Background Art
[0002] At present, the coking industry mainly uses ordinary heat-resistant and high-temperature resistant conveyor belts, which will be damaged after about 6 months of use, resulting in inability to continue to use, seriously affecting work efficiency and benefits. The most common damages include: ① The skeleton material is burned through and delaminated under continuous high temperature; ② The working surface covering layer is aged and cracked under continuous high temperature; ③ The working surface covering layer is burned and hardened; ④ The entire conveyor belt is burned. Therefore, the heat-resistant and high-temperature resistant conveyor belts for coking are generally not effective. The high-temperature coke can easily burn, burn through, or even burn the conveyor belt, resulting in a short lifespan and frequent replacement.
[0003] The invention patent with the publication number CN 101786538 B discloses a production process of a conveyor belt core cloth. The conveyor belt core cloth woven by warp and weft has a surface layer and an inner layer. The warp has 3-6 layers, and the weft consists of two parts. One part is S-shaped and is arranged from top to bottom or from bottom to top from both sides of each layer of warp in sequence, and the other part is S-shaped and is arranged from top to bottom or from bottom to top from both sides of a single warp to cross and pass through the single warp of each layer in sequence. The warp arranged in the surface layer includes a rubber-impregnated forward and reverse twisted rubber-impregnated line and an anti-static line; the upper and lower surfaces of the woven cloth are each compounded with a layer of rubber. However, the rubber layer raw material used in the patent is a conventional rubber material, which does not have significant flame retardancy, and therefore cannot be directly applied to the coking industry.
[0004] The invention patent with publication number CN 116102825 B discloses a halogen-free flame-retardant rubber conveyor belt and its production method, wherein the halogen-free flame-retardant rubber conveyor belt comprises a covering rubber and a skeleton layer, wherein the raw materials of the covering rubber comprise the following components by weight: 30-40 parts of hydrogenated nitrile rubber, 10-20 parts of methyl vinyl phenyl silicone rubber, 50-65 parts of EPDM rubber, 10-20 parts of polyethylene glycol, 20-40 parts of filler, 50-80 parts of microencapsulated aluminum hydroxide, 3-5 parts of cross-linking agent, 20-25 parts of adhesive, and 10-15 parts of antioxidant. However, the obtained conveyor belt cannot meet the requirements of continuous high-temperature dynamic use in the coking process, and its high temperature resistance and heat dissipation are still poor. Summary of the invention
[0005] In order to solve the above-mentioned technical problems, the present invention provides a ceramic conveyor belt for coking and a preparation method thereof, which makes innovative changes in the material and structure of the skeleton material and the performance of the covering layer. It not only has good flame retardancy and high temperature resistance, but also has ceramic properties. It can avoid being scalded or burned through under continuous high-temperature dynamic use, has good heat dissipation, wear resistance and long service life, and has excellent application prospects.
[0006] The purpose of the present invention is achieved through the following technical solutions:
[0007] In the first aspect, the present invention provides a ceramic conveyor belt for coking, which comprises an upper covering rubber layer, an intermediate skeleton layer and a lower covering rubber layer in sequence; the intermediate skeleton layer is a multi-layer fiber woven structure; the upper covering rubber layer is a double-layer structure, comprising an upper layer and a lower layer bonded to the intermediate skeleton layer; in parts by weight, the raw materials of the upper layer comprise 40-60 parts of hydrogenated nitrile rubber, 20-30 parts of chloroprene rubber, 5-10 parts of polyimide, 15-25 parts of a ceramic initiator and 15-25 parts of a flame retardant, the ceramic initiator being composed of ammonium polyphosphate and pentaerythritol in a weight ratio of 2:3, and the raw materials of the lower layer comprise 50-70 parts of ethylene propylene rubber, 30-50 parts of hydrogenated nitrile rubber, 3-4 parts of an adhesive and 10-15 parts of an anti-vulcanization reversion agent.
[0008] The present invention makes changes in the material and structure of the skeleton, adopts a multi-layer integral woven structure, the surface layer uses nylon 66 fiber with good heat resistance, and the inner core layer uses high modulus and low shrinkage polyester fiber, so as to better solve the defects of easy breakage, burn-through and delamination of the skeleton under continuous high temperature industrial and mining conditions.
[0009] The second invention makes a major change in the performance of the covering layer. The working surface covering layer (i.e., the upper covering rubber layer) adopts a double-layer structure. Since the heat-resistant and high-temperature resistant conveyor belts used for coking are generally not effective, the high-temperature coke can easily age, crack and harden the working surface covering layer. Therefore, the upper layer of the upper covering rubber layer is firstly made of chloroprene rubber and hydrogenated nitrile rubber with good flame retardant and wear resistance. Secondly, polyimide, ceramic initiator and flame retardant are added. It can be ceramicized under continuous high temperature conditions, and can be flexibly cracked into a structure similar to a small ceramic piece, which plays a role in heat dissipation and wear resistance when transporting high-temperature coke. The mechanism of ceramicization is as follows: under the initial high-temperature use, the high-temperature coke can easily cause the ordinary heat-resistant conveyor belt working surface covering layer to age and crack, and then under continuous high-temperature use, it is easy to further burn, burn through or even burn; while in the present invention, during continuous high-temperature use, the hydrogenated nitrile rubber and chloroprene rubber in the upper layer of the upper covering rubber layer will promote the dehydration of the organic surface to generate carbonized products under the joint action of ammonium polyphosphate, pentaerythritol and flame retardant, and form a structure similar to a small ceramic piece through bending and breaking. At the same time, ammonium polyphosphate will generate flame-retardant gas to isolate the air and block the supply of oxygen, further enhancing the flame retardancy and preventing the upper layer of the covering rubber from being further burned or burned through; at the same time, the added polyimide and flame retardant can ensure the flame retardancy and high hardness requirements of the upper layer, ensure the hardness of the small ceramic piece, so that it can better play the role of heat dissipation and wear resistance.
[0010] The lower layer of the upper covering rubber layer is made of EPDM rubber and hydrogenated nitrile rubber. EPDM rubber has good high temperature resistance, and the added hydrogenated nitrile rubber can make the lower layer and the upper layer of the upper covering rubber layer more compatible. Adhesives and anti-sulfurization reversion agents are added to firmly adhere the upper ceramic sheet under continuous high temperature conditions, which has a good bonding effect. At the same time, this layer has good high temperature resistance and is soft for long-term use, ensuring the troughing of the conveyor belt.
[0011] Preferably, the raw materials used in the upper layer of the upper cover rubber layer further include 50-60 parts of carbon black, 8-10 parts of paraffin oil, 8-10 parts of zinc oxide, 2-4 parts of antioxidant and 2-4 parts of vulcanizing agent, by weight.
[0012] Preferably, the raw materials used in the lower layer of the upper cover rubber layer further include 50-65 parts of carbon black, 15-25 parts of white carbon black, 15-20 parts of paraffin oil, 6-10 parts of zinc oxide, 3-5 parts of antioxidant and 4-5 parts of vulcanizing agent, by weight.
[0013] Preferably, the average molecular weight of the ammonium polyphosphate is 1000-2000; and the pentaerythritol is ground into a powder of 500-800 mesh.
[0014] Ammonium polyphosphate is a polymer, and limiting its molecular weight is beneficial to better compatibility in the rubber compound. Pentaerythritol is a crystalline powder, and limiting its particle size is convenient for good dispersion in the rubber compound.
[0015] Preferably, the thickness ratio of the upper layer of the upper covering rubber layer, the lower layer of the upper covering rubber layer, the lower covering rubber layer and the middle skeleton layer is 3:3-6:3:3-4.
[0016] Preferably, the middle skeleton layer comprises a surface layer and an inner core layer, the surface layer is woven with nylon fibers, and the inner core layer is woven with polyester fibers.
[0017] Preferably, the raw materials used for the lower covering rubber layer include, by weight: 100 parts of styrene-butadiene rubber, 10-15 parts of zinc oxide, 1-4 parts of stearic acid, 50-60 parts of carbon black, 10-15 parts of aromatic oil, 3-5 parts of antioxidant and 2-3 parts of vulcanizing agent.
[0018] Preferably, the vulcanizing agent used in the upper layer of the upper covering rubber layer is elemental sulfur, and the vulcanizing agent used in the lower layer is a peroxide vulcanizing agent; the vulcanizing agent used in the lower covering rubber layer is a sulfur-containing accelerator.
[0019] In a second aspect, the present invention also provides a method for preparing a ceramic conveyor belt for coking, comprising the following steps: composite molding in the order of an upper covering rubber layer, an intermediate skeleton layer, and a lower covering rubber layer to obtain a belt blank; vulcanizing the belt blank to obtain a ceramic conveyor belt for coking.
[0020] Preferably, the preparation method of the upper layer material in the upper cover rubber layer comprises: preheating and mixing polyimide and hydrogenated nitrile rubber, adding a porcelain initiator, carbon black and paraffin oil to obtain a porcelain initiator masterbatch; preheating chloroprene rubber, adding carbon black, paraffin oil, zinc oxide, an antioxidant and a flame retardant to mix, to obtain a flame retardant masterbatch; after kneading the porcelain initiator masterbatch and the flame retardant masterbatch, adding a vulcanizer and kneading, and cooling to obtain the upper layer material.
[0021] Preferably, the preparation method of the lower layer material in the upper cover rubber layer comprises: preheating hydrogenated nitrile rubber, adding carbon black and paraffin oil to mix, and then adding adhesive to mix to obtain an adhesive masterbatch; preheating ethylene propylene rubber, adding carbon black, paraffin oil, white carbon black, zinc oxide, anti-reversion agent and antioxidant to obtain an anti-reversion agent masterbatch; mixing the adhesive masterbatch and the anti-reversion agent masterbatch, adding a vulcanizing agent to mix, and cooling to obtain the lower layer material.
[0022] Preferably, the preparation method of the lower covering rubber layer material comprises: preheating styrene-butadiene rubber, adding zinc oxide, stearic acid, and an antioxidant for mixing, then adding carbon black and aromatic oil for mixing, then adding a vulcanizing agent for mixing, and after cooling, obtaining the lower covering rubber material.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] (1) The middle skeleton layer adopts a multi-layer integral woven structure. The surface layer uses nylon 66 fiber with good heat resistance, and the inner core layer uses high modulus and low shrinkage polyester fiber, which better solves the defects of easy fracture, breakage, burn-through and delamination of the skeleton under continuous high temperature mining;
[0025] (2) The upper layer of the upper cover rubber layer can be ceramicized under continuous high temperature conditions, and can be flexed and cracked into a structure similar to small ceramic pieces, which plays a role in heat dissipation and wear resistance when transporting high-temperature coke;
[0026] (3) The lower layer of the upper covering rubber layer can firmly adhere the upper ceramic sheet under a continuous high temperature state, achieving a good bonding effect. At the same time, this layer has good high temperature resistance and is soft after long-term use, ensuring the troughability of the conveyor belt;
[0027] (4) By optimizing the structure and formula of the rubber belt, the defects of conveyor belt cracking, hardening, scalding, burning and burning caused by high-temperature coke are greatly improved, which meets the application requirements of the working conditions and improves the service life, providing a high-quality option for energy saving and consumption reduction and increasing benefits in the current coking industry. DETAILED DESCRIPTION
[0028] The technical solution of the present invention is described below with specific embodiments, but the protection scope of the present invention is not limited thereto.
[0029] 1. The ceramic conveyor belt for coking comprises an upper covering rubber layer, an intermediate skeleton layer and a lower covering rubber layer in sequence. The upper covering rubber layer comprises an upper layer and a lower layer, and the lower layer is bonded to the intermediate skeleton layer.
[0030] Middle skeleton layer: an overall fiber woven structure woven from 2-3 layers of warp and weft respectively, including a surface layer and an inner core layer. The surface layer is made of nylon 66 fiber and the inner core layer is made of polyester fiber.
[0031] Upper layer of the upper covering rubber layer: calculated by weight, the raw materials used include 40-60 parts of hydrogenated nitrile rubber, 20-30 parts of chloroprene rubber, 5-10 parts of polyimide, 15-25 parts of porcelain initiator (ammonium polyphosphate and pentaerythritol in a mass ratio of 2:3), 50-60 parts of carbon black, 8-10 parts of paraffin oil, 8-10 parts of zinc oxide, 2-4 parts of antioxidant, 2-4 parts of vulcanizer and 15-25 parts of flame retardant.
[0032] Upper covering rubber layer and lower layer: by weight, the raw materials used include 50-70 parts of EPDM rubber, 30-50 parts of hydrogenated nitrile rubber, 50-65 parts of carbon black, 15-25 parts of white carbon black, 15-20 parts of paraffin oil, 6-10 parts of zinc oxide, 3-5 parts of antioxidant, 10-15 parts of anti-vulcanization reversion agent, 4-5 parts of vulcanizer and 3-4 parts of adhesive.
[0033] Lower covering rubber layer: The raw materials used include, by weight: 100 parts of styrene-butadiene rubber, 10-15 parts of zinc oxide, 1-4 parts of stearic acid, 50-60 parts of carbon black, 10-15 parts of aromatic oil, 3-5 parts of antioxidant and 2-3 parts of vulcanizing agent.
[0034] In a specific embodiment of the present invention, the average molecular weight of ammonium polyphosphate is 1000-2000; pentaerythritol is ground into powder of 500-800 mesh.
[0035] In a specific embodiment of the present invention, the antioxidant is one or more of 4010NA, RD, and MB.
[0036] In a specific embodiment of the present invention, the anti-reversion agent is one or more of hexamethylene-1,6-dithiosulfate disodium salt, 1,3-bis(citralimidemethyl)benzene, and bis-(γ-triethoxysilylpropyl)-tetrasulfide, which can improve the high temperature resistance, aging resistance and fatigue resistance of the vulcanized rubber.
[0037] In a specific embodiment of the present invention, the vulcanizing agent used in the upper layer of the upper cover rubber layer is elemental sulfur (S), and the vulcanizing agent used in the lower layer is a peroxide vulcanizing agent (DCP); the vulcanizing agent used in the lower cover rubber layer is a sulfur-containing accelerator (TMTD).
[0038] In a specific embodiment of the present invention, the flame retardant is one or more of aluminum hydroxide, chlorinated paraffin, and zinc borate.
[0039] In a specific embodiment of the present invention, the adhesive is a peroxide-specific adhesive SL30PR produced by Red Avenue New Materials Company.
[0040] 2. The preparation of the above-mentioned ceramic conveyor belt for coking includes the following steps:
[0041] (1) Upper layer of the upper covering rubber layer: roll the polyimide on an open mill at 60-70°C for 3-5 minutes, then add hydrogenated nitrile rubber and mix for 3-5 minutes, add porcelain initiator, carbon black (half of the total weight of carbon black) and paraffin oil (half of the total weight of paraffin oil) and mix for 1-2 minutes to obtain a porcelain initiator masterbatch; preheat the chloroprene rubber on an open mill at 70-80°C, add Carbon black (remaining weight), paraffin oil (remaining weight), zinc oxide, antioxidant and flame retardant are mixed for 3-5 minutes to obtain flame retardant masterbatch; after mixing the porcelain initiator masterbatch and the flame retardant masterbatch at 60-80℃ for 3-5 minutes, the masterbatch is turned over and the vulcanizer is added, and the masterbatch is mixed at 60-80℃ for 3-5 minutes, the masterbatch is discharged and the sheet is formed, and the upper layer material is obtained after cooling.
[0042] (2) Upper covering rubber layer and lower layer: Roll the hydrogenated nitrile rubber on an open mixing mill at 60-70°C for 3-5 min, add carbon black (half of the total weight of carbon black) and paraffin oil (half of the total weight of paraffin oil) and mix for 1-2 min, then add the adhesive and mix for 1-2 min to obtain an adhesive masterbatch; preheat the ethylene propylene rubber on an open mixing mill to 70-80°C, add carbon black (the remaining weight), paraffin oil (the remaining weight), white carbon black, zinc oxide, an anti-vulcanization reversion agent and an antioxidant and mix for 3-5 min to obtain an anti-vulcanization reversion agent masterbatch; mix the adhesive masterbatch and the anti-vulcanization reversion agent masterbatch at 60-80°C for 3-5 min, then add the vulcanizing agent, mix at 60-80°C for 3-5 min, remove the rubber and sheet it, and cool it to obtain the lower layer material.
[0043] (3) Lower covering rubber layer: Roll the styrene-butadiene rubber on an open mixing mill at 60-70°C for 3-5 min, then add zinc oxide, stearic acid and antioxidant and mix for 1-2 min, then add carbon black and aromatic oil and mix for 3-5 min, add vulcanizer and mix at 60-80°C for 1-2 min, drain the rubber and sheet it, and after cooling, obtain the lower covering rubber material.
[0044] (4) An extruder is used to extrude an upper covering rubber layer, a lower covering rubber layer and a lower covering rubber layer respectively, and a belt blank is obtained by composite molding in the order of the upper covering rubber layer, the lower covering rubber layer, the middle skeleton layer and the lower covering rubber layer; the belt blank is mounted on a corresponding vulcanization plate for vulcanization at a vulcanization temperature of 160°C and a vulcanization time determined according to a specific thickness, and a specific calculation method T=20+1.2*total thickness (the thickness unit is mm, T unit is min, and the calculation result is rounded off) to obtain a ceramic conveyor belt for coking.
[0045] The obtained ceramic conveyor belt for coking was tested according to the test standard shown in Table 1.
[0046] Table 1 Test Standards
[0047]
[0048] Example 1
[0049] The ceramic conveyor belt for coking comprises an upper covering rubber layer, an intermediate skeleton layer and a lower covering rubber layer in sequence. The upper covering rubber layer comprises an upper layer and a lower layer, and the lower layer is bonded to the intermediate skeleton layer.
[0050] Middle skeleton layer: an overall fiber woven structure woven from three layers of warp and weft respectively, including a surface layer and an inner core layer. The surface layer is made of nylon 66 fiber and the inner core layer is made of polyester fiber.
[0051] Upper layer of the upper covering rubber layer: by weight, the raw materials used include 43 parts of hydrogenated nitrile rubber, 30 parts of chloroprene rubber, 8 parts of polyimide, 16 parts of porcelain initiator (ammonium polyphosphate and pentaerythritol in a mass ratio of 2:3, the average molecular weight of ammonium polyphosphate is 2000, and pentaerythritol is ground into 500 mesh powder), 55 parts of carbon black, 8 parts of paraffin oil, 8 parts of zinc oxide, 3 parts of antioxidant (4010NA), 3 parts of vulcanizer (S) and 20 parts of flame retardant (aluminum hydroxide).
[0052] Upper covering rubber layer and lower layer: by weight, the raw materials used include 60 parts of EPDM rubber, 36 parts of hydrogenated nitrile rubber, 60 parts of carbon black, 15 parts of white carbon black, 18 parts of paraffin oil, 10 parts of zinc oxide, 4 parts of antioxidant (4010NA), 10 parts of anti-vulcanization reversion agent (hexamethylene-1,6-disodium dithiosulfate), 4 parts of vulcanizing agent (DCP) and 4 parts of adhesive (SL30PR).
[0053] Lower covering rubber layer: by weight, the raw materials used include 100 parts of styrene-butadiene rubber (SBR1500E), 10 parts of zinc oxide, 1.5 parts of stearic acid, 55 parts of carbon black, 10 parts of aromatic oil, 3 parts of antioxidant (RD+MB) and 2 parts of vulcanizing agent (TMTD).
[0054] The preparation of the above-mentioned ceramic conveyor belt for coking comprises the following steps:
[0055] (1) Upper covering rubber layer: The polyimide is rolled on an open mill at 60°C for 3 min, and then hydrogenated nitrile rubber is added and mixed for 3 min, and a ceramic initiator, carbon black (half of the total weight of carbon black) and paraffin oil (half of the total weight of paraffin oil) are added and mixed for 1 min to obtain a ceramic initiator masterbatch; the chloroprene rubber is rolled on an open mill to preheat at 70°C, and carbon black (the remaining weight), paraffin oil (the remaining weight), zinc oxide, antioxidant and flame retardant are added and mixed for 3 min to obtain a flame retardant masterbatch; the ceramic initiator masterbatch and the flame retardant masterbatch are mixed at 70°C for 3 min, and then the vulcanizer is added and mixed at 70°C for 3 min. The rubber is removed and the sheet is formed, and then cooled to obtain the upper layer material.
[0056] (2) Upper covering rubber layer and lower layer: Roll the hydrogenated nitrile rubber on an open mixing mill at 60°C for 3 min, add carbon black (half of the total weight of carbon black) and paraffin oil (half of the total weight of paraffin oil) and mix for 1 min, then add the adhesive and mix for 1 min to obtain an adhesive masterbatch; preheat the ethylene propylene rubber on an open mixing mill to 70°C, add carbon black (the remaining weight), paraffin oil (the remaining weight), white carbon black, zinc oxide, an anti-reversion agent and an antioxidant and mix for 3 min to obtain an anti-reversion agent masterbatch; mix the adhesive masterbatch and the anti-reversion agent masterbatch at 70°C for 3 min, then add the vulcanizing agent, mix at 70°C for 3 min, remove the rubber and sheet it, and cool it to obtain the lower layer material.
[0057] (3) Lower covering rubber layer: Roll the styrene-butadiene rubber on an open mixing mill at 60°C for 3 min, then add zinc oxide, stearic acid and antioxidant and mix for 1 min, then add carbon black and aromatic oil and mix for 3 min, then add vulcanizer and mix at 70°C for 1 min, then drain the rubber and form sheets, and after cooling, obtain the lower covering rubber material.
[0058] (4) An extruder is used to extrude an upper covering rubber layer, a lower covering rubber layer and a lower covering rubber layer respectively, and a belt blank is obtained by composite molding in the order of the upper covering rubber layer, the lower covering rubber layer, the middle skeleton layer and the lower covering rubber layer; the belt blank (the thickness of the upper covering rubber layer, the lower covering rubber layer, the middle skeleton layer and the lower covering rubber layer are 3 mm, 4 mm, 3 mm and 3 mm respectively, and the total thickness is 13 mm) is installed on a corresponding vulcanization plate and vulcanized at a vulcanization temperature of 160°C and a vulcanization time of 37 min to obtain a ceramic conveyor belt for coking.
[0059] Example 2
[0060] The difference from Example 1 is that the formula ratios of the upper layer of the upper covering glue layer and the lower layer of the upper covering glue layer are different.
[0061] The ceramic conveyor belt for coking comprises an upper covering rubber layer, an intermediate skeleton layer and a lower covering rubber layer in sequence. The upper covering rubber layer comprises an upper layer and a lower layer, and the lower layer is bonded to the intermediate skeleton layer.
[0062] Middle skeleton layer: an overall fiber woven structure woven from three layers of warp and weft respectively, including a surface layer and an inner core layer. The surface layer is made of nylon 66 fiber and the inner core layer is made of polyester fiber.
[0063] Upper layer of the upper covering rubber layer: in parts by weight, the raw materials used include 50 parts of hydrogenated nitrile rubber, 21 parts of chloroprene rubber, 10 parts of polyimide, 20 parts of porcelain initiator (ammonium polyphosphate and pentaerythritol in a mass ratio of 2:3, the average molecular weight of ammonium polyphosphate is 2000, and pentaerythritol is ground into 500 mesh powder), 55 parts of carbon black, 8 parts of paraffin oil, 9 parts of zinc oxide, 4 parts of antioxidant (4010NA), 3 parts of vulcanizing agent (S) and 16 parts of flame retardant (aluminum hydroxide).
[0064] Upper covering rubber layer and lower layer: by weight, the raw materials used include 55 parts of EPDM rubber, 43 parts of hydrogenated nitrile rubber, 60 parts of carbon black, 20 parts of white carbon black, 18 parts of paraffin oil, 10 parts of zinc oxide, 5 parts of antioxidant (4010NA), 15 parts of anti-vulcanization reversion agent (hexamethylene-1,6-disodium dithiosulfate), 4 parts of vulcanizing agent (DCP) and 3 parts of adhesive (SL30PR).
[0065] Lower covering rubber layer: by weight, the raw materials used include 100 parts of styrene-butadiene rubber (SBR1500E), 10 parts of zinc oxide, 1.5 parts of stearic acid, 55 parts of carbon black, 10 parts of aromatic oil, 3 parts of antioxidant (RD+MB) and 2 parts of vulcanizing agent (TMTD).
[0066] Example 3
[0067] The difference from Example 1 is that the formula ratios of the upper glue layer and the lower glue layer are different.
[0068] The ceramic conveyor belt for coking comprises an upper covering rubber layer, an intermediate skeleton layer and a lower covering rubber layer in sequence. The upper covering rubber layer comprises an upper layer and a lower layer, and the lower layer is bonded to the intermediate skeleton layer.
[0069] Middle skeleton layer: an overall fiber woven structure woven from three layers of warp and weft respectively, including a surface layer and an inner core layer. The surface layer is made of nylon 66 fiber and the inner core layer is made of polyester fiber.
[0070] Upper layer of the upper covering rubber layer: by weight, the raw materials used include 60 parts of hydrogenated nitrile rubber, 25 parts of chloroprene rubber, 8 parts of polyimide, 22 parts of porcelain initiator (ammonium polyphosphate and pentaerythritol in a mass ratio of 2:3, the average molecular weight of ammonium polyphosphate is 2000, and pentaerythritol is ground into 500 mesh powder), 50 parts of carbon black, 10 parts of paraffin oil, 8 parts of zinc oxide, 4 parts of antioxidant (4010NA), 3 parts of vulcanizer (S) and 16 parts of flame retardant (aluminum hydroxide).
[0071] Upper covering rubber layer and lower layer: by weight, the raw materials used include 67 parts of EPDM rubber, 33 parts of hydrogenated nitrile rubber, 54 parts of carbon black, 20 parts of white carbon black, 20 parts of paraffin oil, 6 parts of zinc oxide, 5 parts of antioxidant (4010NA), 15 parts of anti-vulcanization reversion agent (hexamethylene-1,6-disodium dithiosulfate), 5 parts of vulcanizing agent (DCP) and 3 parts of adhesive (SL30PR).
[0072] Lower covering rubber layer: by weight, the raw materials used include 100 parts of styrene-butadiene rubber (SBR1500E), 10 parts of zinc oxide, 1.5 parts of stearic acid, 55 parts of carbon black, 10 parts of aromatic oil, 3 parts of antioxidant (RD+MB) and 2 parts of vulcanizing agent (TMTD).
[0073] Comparative Example 1
[0074] The difference from Example 1 is that no polyimide is added to the upper layer of the upper cover glue layer.
[0075] Upper layer of the upper covering rubber layer: in parts by weight, the raw materials used include 43 parts of hydrogenated nitrile rubber, 30 parts of chloroprene rubber, 16 parts of a porcelain initiator (ammonium polyphosphate and pentaerythritol in a mass ratio of 2:3, the average molecular weight of ammonium polyphosphate is 2000, and pentaerythritol is ground into a 500-mesh powder), 55 parts of carbon black, 8 parts of paraffin oil, 8 parts of zinc oxide, 3 parts of an antioxidant (4010NA), 3 parts of a vulcanizing agent (S), and 20 parts of a flame retardant (aluminum hydroxide).
[0076] Comparative Example 2
[0077] The difference from Example 1 is that the porcelain initiator in the upper layer of the upper cover glue layer is changed to ammonium polyphosphate and pentaerythritol in a mass ratio of 3:2.
[0078] Upper layer of the upper covering rubber layer: by weight, the raw materials used include 43 parts of hydrogenated nitrile rubber, 30 parts of chloroprene rubber, 8 parts of polyimide, 16 parts of porcelain initiator (ammonium polyphosphate and pentaerythritol in a mass ratio of 3:2, the average molecular weight of ammonium polyphosphate is 2000, and pentaerythritol is ground into 500 mesh powder), 55 parts of carbon black, 8 parts of paraffin oil, 8 parts of zinc oxide, 3 parts of antioxidant (4010NA), 3 parts of vulcanizer (S) and 20 parts of flame retardant (aluminum hydroxide).
[0079] Comparative Example 3
[0080] The difference from Example 1 is that the weight proportions of hydrogenated nitrile rubber and chloroprene rubber in the upper layer of the upper cover rubber layer are different.
[0081] Upper layer of the upper covering rubber layer: in parts by weight, the raw materials used include 30 parts of hydrogenated nitrile rubber, 43 parts of chloroprene rubber, 8 parts of polyimide, 16 parts of porcelain initiator (ammonium polyphosphate and pentaerythritol in a mass ratio of 2:3, the average molecular weight of ammonium polyphosphate is 2000, and pentaerythritol is ground into 500 mesh powder), 55 parts of carbon black, 8 parts of paraffin oil, 8 parts of zinc oxide, 3 parts of antioxidant (4010NA), 3 parts of vulcanizing agent (S) and 20 parts of flame retardant (aluminum hydroxide).
[0082] Comparative Example 4
[0083] The difference from Example 1 is that the preparation method of the upper layer of the upper cover glue layer is different.
[0084] (1) Upper covering rubber layer: The polyimide is rolled on an open mill at 60°C for 3 min, and then hydrogenated nitrile rubber and chloroprene rubber are added and mixed for 3 min. A ceramic initiator, carbon black, paraffin oil, zinc oxide, antioxidant and flame retardant are added and mixed for 1 min to obtain a masterbatch. After mixing the masterbatch at 70°C for 3 min, the vulcanizer is added and mixed at 70°C for 3 min. The masterbatch is removed and the sheet is formed. After cooling, the upper layer material is obtained.
[0085] Table 2 Heat resistance physical properties test data
[0086]
[0087] Table 3 Flame retardant performance test data
[0088]
[0089] As shown in Tables 2 and 3, the conveyor belt prepared by the present invention can greatly improve the defects of cracking and hardening, scalding, burning and burning of the conveyor belt caused by high-temperature coke, and meet the application requirements of this working condition. Since the upper layer of the upper covering rubber in the conveyor belt structure is the working surface, its formula components are particularly important for the performance of the conveyor belt. In Comparative Examples 1-3, the rubber formula in the upper layer of the upper covering rubber is changed, and the components cannot cooperate to achieve better conveyor belt performance effects, including forming a better small ceramic sheet structure, which will lead to the deterioration of the aging resistance and flame retardant effects of the conveyor belt. In Comparative Example 4, changing the preparation method of the upper layer material of the upper covering rubber will also affect the performance of the conveyor belt. The present invention can make the compatibility and dispersibility between the ceramic initiator and the rubber matrix better through step-by-step mixing, thereby achieving better aging resistance and flame retardant effects.
[0090] The above are only preferred embodiments of the present invention, and are not intended to limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made using the specification of the present invention, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.
Claims
1. A ceramic conveyor belt for coking, characterized in that: The invention comprises an upper covering rubber layer, an intermediate skeleton layer and a lower covering rubber layer in sequence; the intermediate skeleton layer is a multi-layer fiber woven structure; the upper covering rubber layer is a double-layer structure, including an upper layer and a lower layer bonded to the intermediate skeleton layer; the raw materials of the upper layer include 40-60 parts of hydrogenated nitrile rubber, 20-30 parts of chloroprene rubber, 5-10 parts of polyimide, 15-25 parts of porcelain initiator, 15-25 parts of flame retardant, 50-60 parts of carbon black, 8-10 parts of paraffin oil, and 10 parts of oxygen. The raw materials of the lower layer include 50-70 parts of ethylene propylene rubber, 30-50 parts of hydrogenated nitrile rubber, 3-4 parts of adhesive, 10-15 parts of anti-vulcanization agent, 50-65 parts of carbon black, 15-25 parts of white carbon black, 15-20 parts of paraffin oil, 6-10 parts of zinc oxide, 3-5 parts of antioxidant and 4-5 parts of vulcanizer.
2. The ceramic conveyor belt for coking according to claim 1, characterized in that: The average molecular weight of ammonium polyphosphate is 1000-2000.
3. The ceramic conveyor belt for coking according to claim 1, characterized in that: Pentaerythritol is ground into 500-800 mesh powder.
4. The ceramic conveyor belt for coking according to claim 1, characterized in that: The vulcanizing agent used in the upper layer of the upper covering rubber layer is elemental sulfur, and the vulcanizing agent used in the lower layer is a peroxide vulcanizing agent; the vulcanizing agent used in the lower covering rubber layer is a sulfur-containing accelerator.
5. The ceramic conveyor belt for coking according to any one of claims 1 to 4, characterized in that: The thickness ratio of the upper layer of the upper covering rubber layer, the lower layer of the upper covering rubber layer, the lower covering rubber layer and the middle skeleton layer is 3:3-6:3:3-4.
6. The ceramic conveyor belt for coking according to any one of claims 1 to 4, characterized in that: The middle skeleton layer comprises a surface layer and an inner core layer. The surface layer is woven with nylon fibers, and the inner core layer is woven with polyester fibers.
7. The ceramic conveyor belt for coking according to any one of claims 1 to 4, characterized in that: The raw materials used for the lower covering rubber layer include, by weight: 100 parts of styrene-butadiene rubber, 10-15 parts of zinc oxide, 1-4 parts of stearic acid, 50-60 parts of carbon black, 10-15 parts of aromatic oil, 3-5 parts of antioxidant and 2-3 parts of vulcanizing agent.
8. A method for preparing a ceramic conveyor belt for coking as claimed in any one of claims 1 to 7, characterized in that: The method comprises the following steps: compositely molding an upper covering rubber layer, an intermediate skeleton layer and a lower covering rubber layer in order to obtain a belt blank; and vulcanizing the belt blank to obtain a ceramic conveyor belt for coking.
9. The preparation method according to claim 8, characterized in that: The preparation method of the upper layer material in the upper cover rubber layer comprises: preheating and mixing polyimide and hydrogenated nitrile rubber, adding a porcelain initiator, carbon black and paraffin oil to obtain a porcelain initiator masterbatch; preheating chloroprene rubber, adding carbon black, paraffin oil, zinc oxide, an antioxidant and a flame retardant to obtain a flame retardant masterbatch; mixing the porcelain initiator masterbatch and the flame retardant masterbatch, adding a vulcanizer and mixing, and cooling to obtain the upper layer material.
10. The preparation method according to claim 8 or 9, characterized in that: The preparation method of the lower layer material in the upper cover rubber layer comprises: preheating hydrogenated nitrile rubber, adding carbon black and paraffin oil to mix, and then adding adhesive to mix to obtain adhesive masterbatch; preheating ethylene propylene rubber, adding carbon black, paraffin oil, white carbon black, zinc oxide, anti-reversion agent and antioxidant to obtain anti-reversion agent masterbatch; mixing the adhesive masterbatch and the anti-reversion agent masterbatch, adding vulcanizing agent to mix, and cooling to obtain the lower layer material.
Citation Information
Patent Citations
Process for producing core cloth of conveyor
CN101786538B
A halogen-free flame-retardant rubber conveyor belt and its production method
CN116102825B
Firing resistant conveying belt for metal screen and method for producing same
CN101648644A
Ceramic high-temperature-resistant conveyer belt and preparation method thereof
CN107686606A
Energy-saving wear-resistant low-smoke halogen-free fabric-laminated fire-retardant conveyor belt and preparation method thereof
CN110843291A
